2007
DOI: 10.1074/mcp.m600175-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Analysis of Barrett Metaplasia and Esophageal Adenocarcinoma Using Two-dimensional Liquid Mass Mapping

Abstract: Esophageal adenocarcinoma, currently the seventh leading cause of cancer-related death, has been associated with the presence of Barrett metaplasia. The malignant potential of Barrett metaplasia is evidenced by ultimate progression of this condition to invasive adenocarcinoma. We utilized liquid phase separation of proteins with chromatofocusing in the first dimension and nonporous reverse phase HPLC in the second dimension followed by ESI-TOF mass spectrometry to identify proteins differentially expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 36 publications
2
18
0
2
Order By: Relevance
“…The sample number was therefore based on previous esophageal discovery-phase proteomic studies or studies in similar tissue types (1922), and the availability of high quality clinical material.…”
Section: Methodsmentioning
confidence: 99%
“…The sample number was therefore based on previous esophageal discovery-phase proteomic studies or studies in similar tissue types (1922), and the availability of high quality clinical material.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these proteins, such as SCC1, stathmin, calmodulin, fatty-acid binding protein, glutathione S transferase, galectin-7, calgranulin B, tropomyosin, Annexin A1, and nucleoside-diphosphate kinase A, have been reported to be associated with OSCC in previous studies but without clinical validation and in-depth functional research (6 -8). Furthermore eight of the altered expressed proteins, such as Rho GDP dissociation inhibitor 1 (19), proteasome activator complex subunit 2 (20), S100 family proteins (21), translationally controlled tumor protein (22), peroxiredoxin-4 (23), RACK1, calcium-binding protein P22, and protein DJ-1 have been observed to be differentially expressed in cancers from other origins but not previously in OSCC. However, most of these altered proteins have been found to be involved in multiple cellular pathways related to carcinogenesis (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The insight into potential mechanisms underlying the progression from Barrett's metaplasia to EAC was gained by Zhao et al [81], who found that Rho GDP dissociation inhibitor 2, alpha-enolase, lamin A/C, and nucleoside-diphosphate kinase A were upregulated at both mRNA and protein levels in EAC compared to Barrett's metaplasia. The results suggest that the identified proteins play a role in EAC development and may be candidate biomarkers of the progression from Barrett's metaplasia to EAC.…”
Section: Carcinogenesismentioning
confidence: 99%